PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGATASI PERILAKU PHUBBING: TELAAH HERMENEUTIS - Aryanti, Siti; RT, Al-Faiz Muhammad; Muriyanto, Muriyanto (STKIP Pesisir Selatan, 2025)
Phubbing is a social phenomenon that emerged along with the advancement of communication technology and also the massive use of social media that is increasingly widespread in almost all circles, especially teenagers, including in educational environments, which has the potential to damage the quality of communication and form individualistic characters. Phubbing behavior can have an impact on changes in human social interaction patterns and also affect moral and ethical values ​​in behaving towards others, such as empathy, politeness, appreciation, and attention. This study uses a qualitative method through descriptive data analysis, with data collection techniques through library research (writing bibliography) and involving a hermeneutic approach to interpret Islamic texts (Al-Quran and hadith) and Islamic teachings that are relevant to the development of the era in forming social ethics and morals in communicating. The results of the study indicate that PAI has an important role in shaping students' spiritual and social awareness through instilling the values ​​of manners, empathy, self-control, and the use of technology wisely and responsibly. In hermeneutic studies, values ​​such as husn al-khuluq (noble morals), ta'awun (cooperation), and ukhuwah Islamiyah (brotherhood) are key in curbing phubbing behavior.